Mortuary differentiation and social structure in the Middle Helladic Argolid, 2000-1500 B.C - Milka, Eleni (Archaeopress Archaeology, 2023)
In this volume the archaeological, anthropological and radiocarbon data from selected sites of the Middle Helladic period are integrated to determine if there was variation between individual burials, groupings and cemeteries and to reconstruct change through time. This work was done for selective Argive sites, namely Lerna, Asine and Aspis.